Evidence for the Prerequisite Formation of Phenoxyl Radicals in Radical‐Mediated Peptide Tyrosine Nitration In Vacuo. Issue 1 (26th November 2019) - Lai, Cheuk Kuen; Tang, Wai Kit; Siu, Chi‐Kit; Chu, Ivan K.
Abstract: The elementary mechanism of radical‐mediated peptide tyrosine nitration, which is a hallmark of post‐translational modification of proteins under nitrative stress in vivo, has been elucidated in detail by using an integrated approach that combines the gas‐phase synthesis of prototypical molecular tyrosine‐containing peptide radical cations, ion–molecule reactions, and isotopic labeling experiments with DFT calculations. This reaction first involves the radical recombination of . NO2 towards the prerequisite phenoxyl radical tautomer of a tyrosine residue, followed by proton rearrangements, finally yielding the stable and regioselective 3‐nitrotyrosyl residue product. In contrast, nitration with the π‐phenolic radical cation tautomer is inefficient. This first direct experimental evidence for the elementary steps of the radical‐mediated tyrosine nitration mechanism in the gas phase provides a fundamental insight into the regioselectivity of biological tyrosine ortho ‐nitration. Abstract : Determining elementary steps : The elementary mechanism of radical‐mediated peptide tyrosine nitration has been elucidated in detail. Peptide tyrosine nitration resulting in the regioselective 3‐nitrotyrosyl residue requires the availability of the prerequisite phenoxyl radical. By contrast, the π‐phenolic radical cation structure is nonreactive.